Kufi Lari’: the hybrid of Khat Kufi to uphold the Malays’ identity in digital art application / Mohd Amin Mohd Noh … [et al.] - Mohd Noh, Mohd Amin (2015)
Islamic calligraphy is known as Khat was first introduced by the Arabs. There is a variety of Khat including the Kufi, Tuluth and Nasakh. Each types of Khat has its own identity based on several influences such as ornamentals from flora and others nature elements. The influences of Arabic and Islamic pattern are widely spread and implemented in most of the Malays’ culture from centuries ago. The identical influences can be found on wood carving especially from the Malays’ traditional houses and palaces. However, with the development and the evolving of technologies as well as in today’s digital era, there is little effort to uphold the heritage of the Malays’ culture. There are signs of abandonment on several traditional art creation techniques on the most profound artifacts. It would be a great loss for Malays heritage if there is no positive measures are taken to prevent it from extinct. Therefore, the initiative to combine the traditional wood carving motif which is “Awan Larat” and “Larik”; a polishing process in wood carving and with the development and improvement of Kufi Fatimi has resulted in a new hybrid of Khat Kufi known as Kufi Lari’. This study has conducted a pre-post design process of the Kufi Lari’ and it was tested with the application of digital art. Besides that, the collections of data were gathered from a focus group among the academicians and practitioners in the field of graphic design. The results have revealed that Kufi Lari’ in general has an aesthetic value with the influence of ornamentals element even though there is a confusion to identify specifically if the Malays’ identity was embedded based on the ornamentals elements due to the close similarities that has been shown between the Malays’ identity with the Arabic and Islamic influences. Other than that, the use of Kufi Lari’ in the banner used for the International Al-Quran Recital Competition can clearly justify the high readability and legibility of Kufi Lari’ compared to the use of Kufi Muwarraq and Kufi Muzahhar. Ideally, Kufi Lari’ is created objectively to inject the appreciation of the Malays’ traditional wood carving technique (Larik) and Awan Larat motif used in calligraphy with the intention that it can be widely used as art decoration for buildings and environments or delivering message with the application of digital art such as poster, displays and banners.